Evaluating reputation of agents in e-commerce multi-agent environments - Elham, M.; Vimala, B. (2015)
This paper aims to enhance trust in e-commerce multiagent systems by presenting a model to evaluate reputation of provider agents. In this case, we study the most representative trust models in multi-agent systems, which provide different methods for calculating reputation. According to these analysis criteria, a new approach is presented to compute the reputation of provider agents. To evaluate the proposed reputation model, an experimental was carried out in two stages. First, the average accuracy of model in computing the reputation was evaluated by simulating the proposed approach in a multi-agent environment. Second, the performance of the model was compared with a multi-agent environment which does not apply the proposed model. The experimental results show that the proposed reputation model can evaluate the reputation of providers accurately, and the comparison demonstrates that the proposed model can significantly choose the trustworthy provider agent. The ultimate goal of this study is to present a model for computing the reputation of provider agents, and selecting the trustworthy provider based on this computation. We believe that the proposed model will be beneficial to enhance trust in e-commerce environments.